Is the temporary relocation of Gaza residents a solution?: Analysis of Indonesia's Humanitarian Diplomacy Towards the Israel-Palestina Conflict - Yunazwardi, Muhammad Iqbal; Syuryansyah; Rimapradesi, Yulia (Future Science, 2025)
The humanitarian crisis in Gaza, Palestine, has forced international actors to take a stand to promote humanitarian diplomacy, including Indonesia. During Prabowo Subianto’s administration, Indonesia interacted with other countries to formulate humanitarian policies to help the people of Gaza, one of which was the option of temporarily relocating the people of Gaza. This study attempts to rationalise the decision to relocate Gazans temporarily by using Larry Minear and Hazel Smith’s humanitarian diplomacy framework through three approaches: oxymoron, common sense, and a necessary evil. In addition, this study uses a literature review and analysis of news reports and speeches from official statements by the Indonesian government. The results indicate that this decision is controversial. The relocation policy contradicts two aspects: the mandate of the Indonesian Constitution and the desire of the Palestinian people to remain on the land where they have been fighting to defend their rights. However, within the framework of humanitarian diplomacy, the temporary relocation response is a pragmatic foreign policy decision by Indonesia that could be beneficial in advancing humanitarian diplomacy. With the logic of a two-state solution, Indonesia is following the steps of several Western countries and countries in the Middle East to open up adequate space for negotiation, one of which is by recognising Israel as a sovereign state when Palestine is recognised as independent. This policy also positively impacts more open access to aid, which can be effectively distributed directly to war victims. This article concludes that the humanitarian agenda has limited effects because political factors influence the continuity of humanitarian diplomacy in a crisis-affected region.